Squamous Cell Carcinoma Of Left Mandibular Alveolus And Buccal Mucosa – A Clinical Case Report - Dr. Sandhiya M; Dr. Kani Mozhi S A; Dr. Jeya Priyam Vadha P; Dr. Keerthana G; Dr. Pradeep Sankar S; Dr. M. Sathish Kumar (Journal for ReAttach Therapy and Developmental Diversities, 2024)
OSCC represents the predominant form of oral cancer, constituting more than 90% of cases. It stands as the eighth leading cause of cancer-related deaths in the world. The most common site of OSCC is said to be the lips, gingiva, palate and dorsum of the tongue. The potential risk factors of OSCC includes usage of any kind of tobacco, including cigarettes, cigars, pipes, chewing tobacco, betel quid and snuff, heavy alcohol usage and sexually transmitted virus called human papillomavirus (HPV) .This report describes a case of oral squamous cell carcinoma of left mandibular alveolus and buccal mucosa of a 47 year old male patient